Single-atom catalysis toward efficient CO2 conversion to CO and formate products - Su, Xiong (2021)
Simply yet powerfully, single-atom catalysts (SACs) with atomically dispersed metal active centers on supports have received a growing interest in a wide range of catalytic reactions. As a specific example, SACs have exhibited distinctive performances in CO2 chemical conversions. The unique structures of SACs are appealing for adsorptive activation of CO2 molecules, transfer of intermediates from support to active metal sites, and production of desirable products in CO2 conversion. In this Account, we have exemplified our recent endeavors in the development of SACs toward CO2 conversions in thermal catalysis and electrocatalysis. In terms of the support not only stabilizing but also working collaboratively with the single active sites, the proper choice of support is of great importance for its stability, activity, and selectivity in single-atom catalysis. Three distinctive strategies for SAC architectures—lattice-matched oxide supported, heteroatom-doped carbon anchored, and mimetic ligand chelated—are intensively discussed from the perspective of support design for SACs in different reaction environments. To achieve a high-temperature thermal reduction of CO2 to CO, TiO2 (rutile), lattice-matched to the IrO2 active site, was chosen as a support to realize the thermal stability of Ir1/TiO2 SAC, and it shows great capability toward CO2 conversion and excellent selectivity to CO due to the effective block of the over-reduction of CO2 to methane over single Ir active sites. In the electrochemical reduction of CO2 at low temperature, sulfur co-doped N-graphene was developed to achieve unique d9-Ni single atoms on the conductive graphene support, by which not only were the atomic Ni active sites trapped into the matrix of graphene for its stabilization, but also the modulation of electronic configuration of mononuclear Ni centers promoted the CO2 activation through facile electron transfer with an improved electroreduction activity. Inspired by the Ir mononuclear homogeneous catalysts in CO2 hydrogenation to formate, porous organic polymers (POPs) functionalized with a reticular aminopyridine group were purposely fabricated to mimic the homogeneous ligand environment for chelating the Ir single-atom active center, and this quasi-homogeneous Ir1/POP catalyst manifests high efficiency for hydrogenation of CO2 to formate under mild conditions in the liquid phase. Such SACs are of paramount importance for the transformation of CO2, with their coordination environment helping in the activation of CO2. Since the energy barrier for the dissociation of the second C–O bond of CO2 on single-atom sites is very high, these catalysts can give high selectivities toward CO or formate products. Thanks to SACs, the conversion of CO2 has become much easier in various chemical environments.